Przestrzenie powojennego humanizmu. Wystawy Czesława Wielhorskiego (1911–1980) - Tomasz Fudala (Miejsce)
Introducing a radically new political, economic and social order, the communists, who held power in Poland from 1945, could not do without architects. They needed them not only to rebuild the world, which was in moral and material ruin, and not only to design a new architecture to convey new, socialist meanings, but also to communicate with society using the persuasive and effective language of exhibitions. The author analyses C. Wielhorski’s design for museums, fair pavilions in the post-war decades and the phenomenon of his impermanent but innovative projects. He is remembered as the designer of the "Regained Territories Exhibition” (1948) and a creator of posters in art history. Among other projects, Wielhorski is the co-author of remarkable Warsaw displays: the Archeological Museum (1961), the State Ethnographic Museum in Warsaw (1973), Museum of Technology (1975). He was able to apply his visionary ideas to the ephemeral architecture of fair pavilions and exhibitions instead of buildings or permanent urban projects. On the eve of the Cold War, architects were thus entrusted with a medium of crucial significance for state propaganda. The exhibition was a mass medium heavily used by the new regime in domestic and foreign politics. Exhibitions combined architectural skills with those of graphic artists, decorative painters, artisans, and photographers. Commissions from the central government and regional authorities allowed Wielhorski to work outside of architecture – and on a large scale. The fruits of this collaboration were reaped by both sides: the regime had an effective propaganda tool, and the architect profited from lucrative contracts. The price that Wielhorski and artists paid for this patronage was having to follow a pre-defined style, whereas cultural institutions usually granted them much more latitude. Exhibition design, treated by the authorities and the architectural community with greater tolerance than in the case of ‘real’ architecture, proved a niche of relative freedom, where the language of modern forms was allowed. In fact, for Wielhorski, institutions became a space of experimentation and a buffer in relation to the difficulties of reality.